1992 and beyond – the environmental perspectives. (4th August 2014) - Clinton–Davis, Lord
The major issues affecting the growth of a true European community, giving a balanced approach to improving the quality of citizens' lives through the protection and enhancement of the environment and the actions relating that to the 1992 Programme, are addressed in this paper. The main features of the Programme are discussed in brief, with particular reference to the environmental issues. It is argued that the achievement of long–term results relies on its successful introduction, support and, most importantly, continuance, not just as a 'phase' but where environmental protection concerns shall be considered a priority equal to industrial, economic and other major concerns.